The heart's bidding [large type] - Irvin, Kelly (Thorndike Press large print Christian romance series., 2023)
"Together, schoolteacher Rachelle Lapp and auctioneer Toby Miller must face their hardest battle yet: trusting God's plan for their uncertain future. At twenty-nine, auctioneer Toby Miller is a notorious bachelor. But his job keeps him on the road for months out of the year, and he knows no Plain woman could want a marriage that would force her to live and raise children alone. Thankfully, Toby's content to dedicate his life to the family business, especially now that his grandfather is retiring. So why does his heart keep longing for something--or more specifically, someone--he can't have? Rachelle Lapp has already turned down two marriage proposals. Neither promised a future that would bring her more joy than her job as a teacher to Amish children with developmental disabilities, including her brother, Jonah, and Toby's sister, Sadie. But when the parents' committee votes to send her students to the English schools, where they will have access to many more resources, Rachelle finds herself out of a job. She's forced to decide between pursuing her calling far from home and staying near to the man she can't get off her mind. As their families matchmake, Toby and Rachelle realize their jobs may not be all that's holding them back from a future together. They both must learn not only to trust each other, but also trust God's plans for them. But do those plans involve a lifetime together or them going their separate ways?"--